ANALISIS KEUNGGULAN KOMPARATIF PRODUK CENGKEH INDONESIA KE NEGARA ASEAN TAHUN 2015 - IRFA NOVITA SARI, KOMANG; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
The purpose of this study is to measure the competitiveness of Indonesian clove products in ASEAN in 2000-2015 and to analyze the amount of production, exchange rate, and inflation on export value of Indonesian cloves in 2000-2015. In this study used secondary data from 2000-2015 and analyzed using RCA, RCDA, RTA, ISP, and multiple linear analysis techniques. The results of this study suggest that Indonesian clove products have an increased comparative advantage, which is analyzed by RCA to measure on the export side, import RCDAs, export and import RTAs, and multiple linear analysis results for each variable that is the number of influential production positive but not significant to export value of clove indonesia, significant and significant exchange rate to export value of clove indonesia, and inflation which is negative and insignificant to export value.   Keyword : clove export, production, inflation, exchange rate